OPTIMIZATION OF PARAMETERS FOR OBTAINING YACON HONEY IN PILOT PLANT AND EVALUATION OLIGOFRUCTANS - Bautista C., Mario (2004)
This work describes how to obtain honey from yacón (Polimnia sonchifolia) in Pilot Plant. Also we determined that the content of inulin in the proccesed honey is 25.4%.